2018
DOI: 10.1007/s13300-018-0523-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin Degludec and Insulin Glargine U300 on Day-to-Day Fasting Plasma Glucose Variability in Individuals with Type 1 Diabetes: A Multicenter, Randomized, Crossover Study (Kobe Best Basal Insulin Study 2)

Abstract: IntroductionAdministered basal insulin markedly influences the fasting plasma glucose (FPG) level of individuals with type 1 diabetes. Insulin degludec (IDeg) and insulin glargine U300 (IGlar U300) are now available as ultra-long-acting insulin formulations, but whether or how their glucose-stabilizing effects differ remains unclear. We will compare the effects of these basal insulins on parameters related to blood glucose control, with a focus on day-to-day glycemic variability, in individuals with type 1 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The Kobe Best Basal Insulin Study 2 was an 8-week, multicenter, randomized, open-label, cross-over, comparative study involving 46 C-peptide-negative adult outpatients with T1D randomly assigned (1:1) to Gla-300 (first period)/iDeg (second period) or iDeg (first period)/Gla-300 (second period). 24 This study found that iDeg-100 was non-inferior to Gla-300 with respect to fasting glucose SD (assessed using SMBG; primary endpoint). There were also no significant differences in CGM-assessed SD, CV, M-value, mean amplitude of glycemic excursions (MAGE), TIR and mean of daily difference (MODD).…”
Section: Randomized Controlled Trialsmentioning
confidence: 74%
See 1 more Smart Citation
“…The Kobe Best Basal Insulin Study 2 was an 8-week, multicenter, randomized, open-label, cross-over, comparative study involving 46 C-peptide-negative adult outpatients with T1D randomly assigned (1:1) to Gla-300 (first period)/iDeg (second period) or iDeg (first period)/Gla-300 (second period). 24 This study found that iDeg-100 was non-inferior to Gla-300 with respect to fasting glucose SD (assessed using SMBG; primary endpoint). There were also no significant differences in CGM-assessed SD, CV, M-value, mean amplitude of glycemic excursions (MAGE), TIR and mean of daily difference (MODD).…”
Section: Randomized Controlled Trialsmentioning
confidence: 74%
“…[15][16][17][18][19] Several randomized controlled trials (RCTs) involving Gla-300 in people living with T1D have included measures of glycemic variability. [20][21][22][23][24] In addition, one study has reported real-world evidence (RWE) on glycemic variability in people treated with Gla-300. 25 There is a lack of longer term prospective studies using CGM and of studies comparing second-generation basal insulin.…”
Section: Glycemic Variability and Guidance On The Use And Interpretat...mentioning
confidence: 99%
“…The study protocol was described previously 28 . In brief, participants had to satisfy all the inclusion criteria and not meet any exclusion criteria, as described in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…As described in detail previously, 28 according to a preliminary analysis of day‐to‐day variability in FBG levels for individuals with type 1 diabetes treated with IDeg, the mean and SD values for the SD of FBG in 30 patients over 7 consecutive days were calculated to derive the SD for the intra‐patient difference. The non‐inferiority margin was set as 20 mg/dL (1.1 mmol/L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation